STUDI PROFITABILITAS USAHATANI DAN PEMASARAN TOMAT DI KECAMATAN SEMBALUN KABUPATEN LOMBOK TIMUR - Nur Imamsah Suryadi (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2023)
This article discusses the Profitability of Tomato Farming and Marketing in Sembalun District, East Lombok Regency. The method used in this study is a descriptive method with the unit of analysis used is tomato farming in Sembalun District. The research area was determined by purposive sampling with the determination of farmer respondents using the accidental sampling method and the determination of merchant respondents using the snowball sampling method. After going through a long process, the authors found that 1) The average yield of tomato farming in Sembalun District was 2,544 kg/LLG or 22,754 kg/Ha with an average price of Rp. 5.500/kg. Production costs incurred an average of Rp. 4,728,988/LLG or Rp. 55,438,772/Ha and farm income obtained on average is Rp. 9.264.295/LLG or Rp. 69,707,966/Ha. 2) The profitability of tomato farming in Sembalun District is an average of 143% during the season, where the profitability value is greater than the Bank Indonesia interest rate that has been set at 3% per month. 3) There are three marketing channels for tomato farming in Sembalun District, namely: (i) the first marketing channel: from producer farmers directly to final consumers with a sales volume of 1,677 Kg or 2%; (ii) two marketing channels, namely from producers to retailers then final consumers with a sales volume of 38.953 Kg or 51% and (iii) three marketing channels, namely from producers to collectors then to wholesalers, to retailers and finally to wholesalers. consumers with a sales volume of 35,697 Kg or 47%. 4) Marketing of tomatoes in Sembalun District, is included in the efficient criteria for channels one, two and three because the share price received by farmers is >60%.